New light on changes in the number and function of blood platelets stimulated by cocoa and its products - Olas, Beata (Frontiers in Pharmacology, 2024)
Hyperactivation of blood platelets, one of the causes of heart attack, and other cardiovascular diseases (CVDs), is influenced by various dietary components, including phenolic compounds from vegetables, fruits, teas, wines, cocoa and its products, including chocolate. The present paper sheds new light on the effect of cocoa and its products, especially dark chocolate, on the number and function of blood platelets, and the anti-platelet activity of their constituent phenolic compounds. A review was performed of papers identified in various electronic databases, including PubMed, Science Direct, Scopus, Web of Knowledge, and Google Scholar, with the aim of determining whether their anti-platelet activity may serve as part of a sweet strategy in countering CVDs. Various studies demonstrate that cocoa consumption, especially in the form of dark chocolate, with a high flavanol concentration, has anti-platelet activity and may play a significant role in cardioprotection; they also note that cocoa consumption may be a good strategy in diminishing cardiovascular risk, including hyperactivation of blood platelets.